C. McGinn. The concept of a person / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность", 2024)
The essay contains a critique of the metaphysical ways to use of the term ‘person’. Since the term does not designate any natural kind, philosophers must abandon the question ‘what constitutes the continued existence of a person?’. It’s just a bad question. All well-defined questions about identity (‘what is human animal identity?’, ‘what is human mind identity?’, and so on) should formulate only in terms of natural kinds.